2005
DOI: 10.1007/s10681-005-7877-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-maturity α-amylase and incipient sprouting in UK winter wheat, with special reference to the variety Rialto

Abstract: In 1998 and 1999 the UK winter wheat variety Rialto produced unexpected low Hagberg falling numbers that could not be directly linked to sprouting. It was proposed that these reductions in quality could be due to pre-maturity α-amylase activity (PMAA). The problem was not identified during the selection and commercial development stages. Our study tested the hypothesis that the variety Rialto is PMAA-susceptible. Analysis was done on 13 year-location combinations of field grown Rialto. Together, visual and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In addition, it was suggested that the elevated temperatures during harvest period promoted grain drying by rapid evaporation. [ 48 ] Such conditions may favor the harvest of mature grains before the induction of α‐amylase by precipitation at harvest time. [ 45 ] Another possible explanation is that a temperature of 15 °C lead to delay in wheat germination compared to 20 °C, [ 49 ] since the germination inhibitor (e.g., abscisic acid) is maintained in the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was suggested that the elevated temperatures during harvest period promoted grain drying by rapid evaporation. [ 48 ] Such conditions may favor the harvest of mature grains before the induction of α‐amylase by precipitation at harvest time. [ 45 ] Another possible explanation is that a temperature of 15 °C lead to delay in wheat germination compared to 20 °C, [ 49 ] since the germination inhibitor (e.g., abscisic acid) is maintained in the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Premature breaking of dormancy can result in PHS of spikes in wet weather conditions. PHS is a major cause of excess α-amylase activity (AA), which impairs grain quality since enzymatic hydrolysis of starch during food manufacture can lead to processing problems and unsatisfactory end products (Graybosch et al 2000; Lunn et al 2001; Mares et al 2002; Tjin Wong Joe et al 2005). Much research on wheat grains has proved that there are a number of additional causes for the deterioration of meal properties, which reflects low falling number.…”
Section: Introductionmentioning
confidence: 99%
“…Much research on wheat grains has proved that there are a number of additional causes for the deterioration of meal properties, which reflects low falling number. These include late maturity α-amylase (LMA) (Mrva and Mares 1996a, b, 1999, 2002, 2008), also known as prematurity α-amylase (PMAA) in the UK (Lunn et al 2001; Tjin Wong Joe et al 2005), and retained pericarp α-amylase (RPAA) (Lunn et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In LMA-susceptible varieties, PCD symptoms are present in individual cells or cell patches in random locations throughout the aleurone (Mrva et al 2006). Previous studies have also shown that LMA initially affected cells near the grain crease in UK varieties (Major 1999;Lunn et al 2001;Joe et al 2005). The low percentage of affected cells agrees with the relatively lower levels of α-amylase when mature LMA-affected varieties are compared to sprouted grain over time.…”
Section: Biochemical Mechanisms Of Lmamentioning
confidence: 65%
“…The underlying biochemical mechanisms associated with the induction of LMA are currently unknown. Studies have provided insights into the expression and protein accumulation of α-amylase during this developmental event (Gale et al 1987;Mrva and Mares 1996c, 1999, 2001aJoe et al 2005;Mrva et al 2006Mrva et al , 2009Farrell and Kettlewell 2008;Barrero et al 2013Barrero et al , 2020Farrell et al 2013;Kondhare et al 2013Kondhare et al , 2014Cheng et al 2014;Mieog et al 2017;Derkx and Mares 2020). In LMA-susceptible wheat varieties, the relative expression and protein abundance of high pI α-amylase increased during late grain development, at 20 days postanthesis (dpa) (Barrero et al 2013).…”
Section: Biochemical Mechanisms Of Lmamentioning
confidence: 99%